Water-based two-component electrostatic spraying varnish finish paint and preparation method thereof

By using hydroxyl-containing and hydroxy-free aqueous polyurethane dispersions and modified nano-aluminum silicate in aqueous electrostatic spray varnish, the problem of bubble and pinhole defects in aqueous electrostatic spray varnish during drying is solved, and the smoother and more resistant Grinding coating effect.

CN119192973APending Publication Date: 2024-12-27HUASU (GUANGZHOU) ENVIRONMENTAL PROTECTION NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534330.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Water-based electrostatic spray varnish is prone to expose bubbles and pinhole defects during drying, resulting in uneven surfaces and lack of covering and dispersing effects of pigment particles, making them more susceptible to environmental factors.

Method used

Using aqueous two-component electrostatic spray varnish topcoat, including hydroxyl-containing aqueous polyurethane dispersions and hydroxyl-free aqueous polyurethane dispersions, combined with modified nano-aluminum silicate and polyisocyanate, optimize the coating structure through specific preparation methods to reduce air bubbles and pinhole formation.

Benefits of technology

The leveling and drying speed of the coating are optimized, bubbles and pinholes are generated, the filling and covering capacity of the coating is improved, and the flatness and wear resistance of the surface are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192973A_ABST
    Figure CN119192973A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based bi-component electrostatic spraying varnish finish paint, which is characterized by comprising a component A and a component B, 100 parts by weight of a hydroxyl-containing aqueous polyurethane dispersion; 10 to 40 parts by weight of a hydroxyl-free aqueous polyurethane dispersion; 1-3 parts by weight of modified aluminum silicate; 0.2-2 parts by weight of a conductive regulator; 10 to 30 parts by weight of deionized water; the component B comprises the following components in parts by weight: 20-50 parts of polyisocyanate; and 5-20 parts by weight of propylene glycol methyl ether acetate. The hydroxyl-free polyurethane dispersion provided by the invention possibly has different molecular structures and surface tension, and forms complementation with a hydroxyl-containing dispersion, so that the leveling property and the drying speed of a coating can be optimized, and bubbles and pinholes are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a water-based two-component electrostatic spray varnish topcoat and a preparation method thereof. Background Art

[0002] As an efficient and environmentally friendly coating method, electrostatic spraying technology is widely used in the surface treatment of various substrates. This technology uses the principle of electrostatic adsorption to make the paint particles evenly deposit on the surface of the substrate under the action of the electric field to form a smooth and uniform coating. However, in actual applications, different types of paint will show different characteristics and challenges during the electrostatic spraying process.

[0003] Electrostatic spraying uses the principle of electrostatic adsorption to evenly spray the paint on the substrate. However, due to its high transparency and high surface tension, varnish may be more susceptible to environmental factors such as humidity and temperature during the electrostatic spraying process, resulting in poor drying and paint disease. Water-based electrostatic spray solid color paint contains pigment particles, which play a filling and thickening role in the paint and can improve the rheology and construction performance of the paint. The presence of pigment particles can reduce the formation of bubbles and pinholes in the paint because they can act as nucleation points to help bubbles disperse and escape in the paint.

[0004] Since water-based electrostatic spray varnish does not contain pigments, it has a high degree of transparency. While ensuring surface hardness and wear resistance, the varnish is more likely to expose defects such as bubbles and pinholes during the drying process due to the lack of covering and dispersion effects of pigment particles. This problem urgently needs to be improved. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a water-based two-component electrostatic spray varnish topcoat and a preparation method thereof, which solves the problems raised in the above-mentioned background technology.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A water-based two-component electrostatic spray varnish topcoat, comprising component A and component B;

[0010] 100 parts by weight of hydroxyl-containing aqueous polyurethane dispersion

[0011] 10-40 parts by weight of hydroxyl-free aqueous polyurethane dispersion

[0012] 1-3 parts by weight of modified aluminum silicate

[0013] Conductivity regulator 0.2-2 parts by weight

[0014] Deionized water 10-30 parts by weight

[0015] Group B is composed of:

[0016] Polyisocyanate 20-50 parts by weight

[0017] Propylene glycol methyl ether acetate 5-20 parts by weight.

[0018] The mass content of hydroxyl groups in the hydroxyl-containing aqueous polyurethane dispersion is 4.5%-6.5%.

[0019] The varnish topcoat also includes the following components:

[0020] Thickener 0.1-1 parts by weight

[0021] Wetting agent 0.1-1 weight part

[0022] Leveling agent 0.1-1 parts by weight

[0023] Defoamer 0.1-1 parts by weight

[0024] Ultraviolet light absorber 0.1-1 part by weight.

[0025] The polyisocyanate consists of 10-30 parts by weight of HDI trimer, 5-10 parts by weight of isophorone diisocyanate, and 5-10 parts by weight of blocked polyisocyanate.

[0026] The preparation method of modified nano aluminum silicate is as follows:

[0027] S01: Pretreatment of Nano-aluminum Silicate

[0028] The nano aluminum silicate powder is placed in a sufficient amount of sodium hydroxide solution with a mass fraction of 1% to 5% and stirred to mix well for surface activation treatment;

[0029] This is followed by water washing to remove excess sodium hydroxide;

[0030] Then, drying treatment is performed to obtain pretreated nano aluminum silicate for standby use;

[0031] S02: Thermal reaction treatment

[0032] The nano aluminum silicate powder prepared in S01 is placed in a high temperature environment of 300-350°C for thermal reaction treatment for 20-30 minutes;

[0033] After the thermal reaction is completed, slowly cool to 200-230°C at a rate of 2-3°C / min and keep at this temperature for 10-30 minutes;

[0034] Finally, cool to room temperature at a rate of 4-6°C / min and keep warm for later use;

[0035] S03: Blending and modification

[0036] Take 5-8 parts of S02 nano aluminum silicate powder, 2-4 parts of silane coupling agent, 0.5-1 parts of nitrate solution and 8-12 parts of surfactant and mix them together;

[0037] The mixture is subjected to ultrasonic blending to ensure that each component is fully dispersed and uniformly mixed;

[0038] After the blending ultrasonic treatment is completed, it is set aside;

[0039] S04: High temperature modification treatment

[0040] The reserved nano aluminum silicate powder of S03 is heated to 400-500°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min. After cooling to room temperature, it is heated to 500-600°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min. After cooling, the modified nano aluminum silicate is obtained.

[0041] After the water washing in S01, the method further comprises the following steps: mixing the pretreated nano-aluminum silicate with a sufficient amount of silicic acid solution with a mass fraction of 2%-5% to perform surface silicification treatment.

[0042] The nitrate solution is selected from one or more of a cerium nitrate solution, a zirconium nitrate solution, and a lanthanum nitrate solution.

[0043] The silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane.

[0044] A method for preparing a water-based two-component electrostatic spray varnish topcoat, wherein the electrostatic spray varnish topcoat comprises a component A and a component B;

[0045] 100 parts by weight of hydroxyl-containing aqueous polyurethane dispersion

[0046] 10-40 parts by weight of hydroxyl-free aqueous polyurethane dispersion

[0047] 1-3 parts by weight of modified aluminum silicate

[0048] Conductivity regulator 0.2-2 parts by weight

[0049] Deionized water 10-30 parts by weight

[0050] Group B is composed of:

[0051] Polyisocyanate 20-50 parts by weight

[0052] Propylene glycol methyl ether acetate 5-20 parts by weight;

[0053] The A and B components are mixed evenly and packaged separately to obtain a water-based two-component electrostatic spray varnish topcoat.

[0054] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0055] The hydroxyl-free polyurethane dispersion of the present invention may have different molecular structures and surface tensions, and complements the hydroxyl-containing dispersion, thereby optimizing the leveling and drying speed of the coating and further reducing the generation of bubbles and pinholes.

[0056] The particle structure of the nano-modified aluminum silicate of the present invention is more compact and orderly, thereby improving its filling and covering capabilities. This optimized structure enables the nano-modified aluminum silicate to better fill tiny pores and defects in the coating, effectively reducing the formation of pinholes. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 Part of the experimental results of Examples 1-3.

[0058] Figure 2 Part of the experimental results of Comparative Examples 1-2 are shown.

[0059] Figure 3 Part of the experimental results of Comparative Examples 3-5 are shown.

[0060] Figure 4 Part of the experimental results of Comparative Examples 6-8 are shown. DETAILED DESCRIPTION

[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] In an embodiment of the present invention, the water-based two-component electrostatic spray varnish topcoat comprises component A and component B;

[0063] 100 parts by weight of hydroxyl-containing aqueous polyurethane dispersion

[0064] 10-40 parts by weight of hydroxyl-free aqueous polyurethane dispersion

[0065] 1-3 parts by weight of modified aluminum silicate

[0066] Conductivity regulator 0.2-2 parts by weight

[0067] Thickener 0.1-1 parts by weight

[0068] Wetting agent 0.1-1 weight part

[0069] Leveling agent 0.1-1 parts by weight

[0070] Defoamer 0.1-1 parts by weight

[0071] Ultraviolet light absorber 0.1-1 parts by weight

[0072] Deionized water 10-30 parts by weight

[0073] Group B is composed of:

[0074] Polyisocyanate 20-50 parts by weight

[0075] Propylene glycol methyl ether acetate 5-20 parts by weight.

[0076] In an embodiment of the present invention, the polyisocyanate is composed of 10-30 parts by weight of HDI trimer, 5-10 parts by weight of isophorone diisocyanate, and 5-10 parts by weight of blocked polyisocyanate.

[0077] The preparation method of modified nano aluminum silicate is as follows:

[0078] S01: Pretreatment of Nano-aluminum Silicate

[0079] The nano aluminum silicate powder is placed in a sufficient amount of sodium hydroxide solution with a mass fraction of 1% to 5% and stirred to perform surface activation treatment;

[0080] This is followed by water washing to remove excess sodium hydroxide;

[0081] Then, drying treatment is performed to obtain pretreated nano aluminum silicate;

[0082] Then, the pretreated nano aluminum silicate is mixed thoroughly in a sufficient amount of silicate solution with a mass fraction of 2% to 5% to perform surface siliconization treatment;

[0083] Finally, wash and dry again for later use;

[0084] S02: Thermal reaction treatment

[0085] The nano aluminum silicate powder prepared in S01 is placed in a high temperature environment of 300-350°C for thermal reaction treatment for 20-30 minutes;

[0086] After the thermal reaction is completed, slowly cool to 200-230°C at a rate of 2-3°C / min and keep at this temperature for 10-30 minutes;

[0087] Finally, cool to room temperature at a rate of 4-6°C / min and keep warm for later use;

[0088] S03: Blending and modification

[0089] Take 5-8 parts of S02 nano aluminum silicate powder, 2-4 parts of silane coupling agent, 0.5-1 parts of nitrate solution and 8-12 parts of surfactant and mix them together;

[0090] The mixture is subjected to ultrasonic blending to ensure that each component is fully dispersed and uniformly mixed;

[0091] After the blending ultrasonic treatment is completed, it is set aside;

[0092] S04: High temperature modification treatment

[0093] The S03 reserved nano aluminum silicate powder is heated to 400-500°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min. After cooling to room temperature, it is heated to 500-600°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min, wherein the mass content of oxygen is 1%-5%. After cooling, the modified nano aluminum silicate is obtained.

[0094] As a preferred embodiment, the nitrate solution is selected from one or more of a cerium nitrate solution, a zirconium nitrate solution, and a lanthanum nitrate solution.

[0095] As a preferred embodiment, the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, and vinyltriethoxysilane.

[0096] The high temperature treatment of the present invention can further activate the surface of the nano aluminum silicate, making the active sites on the surface more exposed and active. This helps the nano aluminum silicate to better interact with other components such as silane coupling agents, nitrate solutions and surfactants in the subsequent blending and modification treatment. Silicic acid treatment can form a protective layer of silicate on the surface of the nano aluminum silicate, and this protective layer can promote the nano aluminum silicate to better interact with other components such as silane coupling agents, nitrate solutions and surfactants.

[0097] The metal elements on the surface of the modified nano-aluminum silicate of the present invention may serve as catalytic active centers, adsorb reactant molecules, reduce the activation energy of the reaction, and cooperate with blocked polyisocyanates to further increase the crosslinking density of the coating. By adjusting the ratio of oxygen and nitrogen, the degree of oxidation on the surface of the nano-aluminum silicate can be accurately controlled, thereby controlling the crosslinking density of the coating in the later stage.

[0098] In the following examples and comparative examples:

[0099] Hydroxyl-containing waterborne polyurethane dispersion:

[0100] Covestro Bayhydrol UH 2592 has a hydroxyl content of 2.1%, a solid content of 45%, and a viscosity of 500 mPa·s.

[0101] Archroma's Mowipur 1212 has a hydroxyl content of 4.7%, a solid content of 32%, and a viscosity of 4500 mPa·s.

[0102] Hydroxyl-free waterborne polyurethane dispersions:

[0103] BASF Joncryl U 4188, solid content 38%, viscosity 50mPa·s.

[0104] BASF Joncryl U 4190, solid content 36.5%, viscosity 80mPa·s.

[0105] Covestro DLN, solid content 50%, viscosity 400mPa·s.

[0106] Covestro Bayhydrol U 2757, solid content 45%, viscosity 800mPa·s.

[0107] Conductivity regulator: Baytron P from Covestro

[0108] Thickener: Rohm and Haas Acrysol RM-2020NPR

[0109] Wetting Agents 110(BYK Chemical)

[0110] Leveling agent -333(BYK Chemical)

[0111] Defoaming agent A30(Nouryon)

[0112] UV absorber 328(BASF)

[0113] Propylene glycol methyl ether acetate 5-20 parts by weight.

[0114] HDI trimer VPLS2151 (Covestro)

[0115] IPDI (isophorone diisocyanate) T 1890 (Evonik)

[0116] Blocked polyisocyanate XP 2655 (Covestro)

[0117] Nano aluminum silicate Hubei Chengfeng Chemical, average particle size 400 nanometers.

[0118] The preparation method of modified nano aluminum silicate is as follows:

[0119] S01: Pretreatment of Nano-aluminum Silicate

[0120] The nano-aluminum silicate powder is placed in a sufficient amount of a 2% by mass sodium hydroxide solution and stirred to be uniformly mixed for surface activation treatment;

[0121] This is followed by water washing to remove excess sodium hydroxide;

[0122] Then, drying treatment is performed to obtain pretreated nano aluminum silicate;

[0123] Then, the pretreated nano aluminum silicate is mixed thoroughly in a sufficient amount of 3% by mass silicate solution to perform surface siliconization treatment;

[0124] Finally, wash and dry again for later use;

[0125] S02: Thermal reaction treatment

[0126] The nano-aluminum silicate powder prepared in S01 was placed in a high temperature environment of 350°C for a thermal reaction treatment for 30 minutes;

[0127] After the thermal reaction was completed, the mixture was slowly cooled to 230 °C at a rate of 3 °C / min and kept at this temperature for 30 min;

[0128] Finally, cool to room temperature at a rate of 6°C / min and keep warm for later use;

[0129] S03: Blending and modification

[0130] Take 6 parts of S02 nano-aluminum silicate powder, 3 parts of γ-aminopropyl triethoxysilane, 1 part of cerium nitrate solution and 10 parts of octylphenol polyoxyethylene ether (OP-7) and mix them together;

[0131] The mixture is subjected to ultrasonic blending to ensure that each component is fully dispersed and uniformly mixed;

[0132] After the blending ultrasonic treatment is completed, it is set aside;

[0133] S04: High temperature modification treatment

[0134] The S03 reserved nano aluminum silicate powder is heated to 500°C in an inert atmosphere and reacted for 2 hours at a heating rate of 3°C / min. After cooling to room temperature, it is heated to 600°C in an inert atmosphere and reacted for 2 hours at a heating rate of 5°C / min. After cooling, the modified nano aluminum silicate is obtained.

[0135] Example 1

[0136] Archroma Mowipur 1212 hydroxyl content 4.5% 100 parts by weight

[0137] BASF Joncryl U 4188 15 parts by weight

[0138] BASF Joncryl U 4190 15 parts by weight

[0139] 2 parts by weight of modified nano aluminum silicate, obtained by the aforementioned preparation method.

[0140] Conductivity regulator Baytron P from Covestro 0.5 parts by weight

[0141] Thickener Rohm and Haas Acrysol RM-2020NPR 0.5 parts by weight

[0142] Wetting Agents 110 (BYK Chemical) 0.5 parts by weight

[0143] Leveling agent -333 (BYK Chemical) 0.5 parts by weight

[0144] Defoaming agent A30 (Nouryon) 0.5 parts by weight

[0145] UV absorber 328 (BASF) 0.5 parts by weight

[0146] Propylene glycol methyl ether acetate 10 parts by weight

[0147] HDI trimer VPLS2151 (Covestro) 20 parts by weight T 1890 (Evonik) 10 parts by weight blocked polyisocyanate XP 2655 (Covestro) 10 parts by weight.

[0148] Example 2

[0149] Archroma Mowipur 1212 hydroxyl content 4.5% 100 parts by weight

[0150] Covestro DLN 20 parts by weight

[0151] Covestro Bayhydrol U 2757 15 parts by weight

[0152] 2 parts by weight of modified nano aluminum silicate, obtained by the aforementioned preparation method.

[0153] Conductivity regulator Baytron P from Covestro 0.5 parts by weight

[0154] Thickener Rohm and Haas Acrysol RM-2020NPR 0.5 parts by weight

[0155] Wetting Agents 110 (BYK Chemical) 0.5 parts by weight

[0156] Leveling agent -333 (BYK Chemical) 0.5 parts by weight

[0157] Defoaming agent A30 (Nouryon) 0.5 parts by weight

[0158] UV absorber 328 (BASF) 0.5 parts by weight

[0159] Propylene glycol methyl ether acetate 10 parts by weight

[0160] HDI trimer VPLS2151 (Covestro) 30 parts by weight T 1890 (Evonik) 7 parts by weight blocked polyisocyanate XP 2655 (Covestro) 8 parts by weight.

[0161] Example 3

[0162] Archroma Mowipur 1212 hydroxyl content 4.5% 100 parts by weight

[0163] Covestro DLN 20 parts by weight

[0164] Covestro Bayhydrol U 2757 10 parts by weight

[0165] 2 parts by weight of modified nano aluminum silicate, obtained by the aforementioned preparation method.

[0166] Conductivity regulator Baytron P from Covestro 0.5 parts by weight

[0167] Thickener Rohm and Haas Acrysol RM-2020NPR 0.5 parts by weight

[0168] Wetting Agents 110 (BYK Chemical) 0.5 parts by weight

[0169] Leveling agent -333 (BYK Chemical) 0.5 parts by weight

[0170] Defoaming agent A30 (Nouryon) 0.5 parts by weight

[0171] UV absorber 328 (BASF) 0.5 parts by weight

[0172] Propylene glycol methyl ether acetate 10 parts by weight

[0173] HDI trimer VPLS2151 (Covestro) 20 parts by weight T 1890 (Evonik) 10 parts by weight blocked polyisocyanate XP 2655 (Covestro) 10 parts by weight.

[0174] Comparative Example 1

[0175] Same as Example 1, but without adding the following components:

[0176] BASF Joncryl U 4188 15 parts by weight BASF Joncryl U 4190 15 parts by weight.

[0177] Comparative Example 2

[0178] Same as Example 1, but:

[0179] Archroma Mowipur 1212 hydroxyl content 4.5% 100 parts by weight

[0180] HDI trimer VPLS2151 (Covestro) 20 parts by weight

[0181] T 1890 (Evonik) 10 parts by weight

[0182] Blocked polyisocyanate XP 2655 (Covestro) 10 parts by weight

[0183] Replace with:

[0184] Covestro Bayhydrol UH 2592 Hydroxyl content 2.1% 100 parts by weight

[0185] HDI trimer VPLS2151 (Covestro) 10 parts by weight

[0186] T 1890 (Evonik) 5 parts by weight

[0187] Blocked polyisocyanate XP 2655 (Covestro) 5 parts by weight.

[0188] Comparative Example 3

[0189] Same as Example 1, without adding:

[0190] Blocked polyisocyanate XP 2655 (Covestro) 10 parts by weight.

[0191] Comparative Example 4

[0192] The same as Example 1, without adding nano aluminum silicate.

[0193] Comparative Example 5

[0194] Same as Example 1, except that 2 parts by weight of modified nano-aluminum silicate and blocked polyisocyanate were not added. XP 2655 (Covestro) 10 parts by weight.

[0195] Comparative Example 6

[0196] The same as Example 1, the nano aluminum silicate used is replaced by nano aluminum silicate prepared in S01.

[0197] Comparative Example 7

[0198] The same as Example 1, the nano aluminum silicate used is replaced by nano aluminum silicate with S02 as a backup.

[0199] Comparative Example 8

[0200] The same as Example 1, the nano-aluminum silicate used is replaced by nano-aluminum silicate with S03 as spare.

[0201] Use sandpaper to polish the surface of the wooden board (disk bean) to remove dust, dirt and uneven parts. Use a special dust removal cloth to clean the surface of the wooden board to ensure that there is no residue. Spray primer (use Shenzhen Huihuang Paint Company's transparent closed primer XY-WT4603-2, add 10wt% deionized water before spraying), coating amount 60g / m 2 , and then dried to obtain a wood board with primer. A wood board with primer and no surface defects is selected, and the water-based two-component electrostatic spray varnish topcoat in the embodiment of the present invention and the comparative example is sprayed on the wood board with primer by electrostatic spraying. After spraying, the wood board is leveled for 30 minutes and then put into a drying room for forced baking at 60-80°C for 60 minutes.

[0202] Spraying parameters:

[0203] Electrostatic high voltage: 60-90kV, adjusted according to the characteristics of the paint and the model of the spray gun.

[0204] Flow rate pressure: 0.30-0.55MPa, ensure uniform spraying of powder.

[0205] Atomization pressure: 0.30-0.45MPa, keep the coating thickness uniform.

[0206] Distance from spray gun mouth to workpiece: 150-300mm.

[0207] After drying, take out the board and let it cool naturally to room temperature. Perform an appearance inspection on the dried board, including coating flatness, color and glossiness. Perform a pencil hardness test and abrasion resistance test on the board.

[0208] The performance test results of the embodiments and comparative examples are shown in Table 1:

[0209] Table 1

[0210] Surface state Pencil hardness Abrasion resistance / times Test Standards Visual GB / T 6739-2006 ASTMF2357-04 Example 1 The surface is smooth without bubbles or pinholes 4H 380 Example 2 The surface is smooth without bubbles or pinholes 4H 350 Example 3 The surface is smooth without bubbles or pinholes 4H 355 Comparative Example 1 The surface is uneven 3H 365 Comparative Example 2 The surface is uneven 2H 250 Comparative Example 3 The surface is uneven 2H 210 Comparative Example 4 The surface is uneven H 150 Comparative Example 5 The surface is uneven H 130 Comparative Example 6 The surface is uneven H 170 Comparative Example 7 The surface is uneven H 180 Comparative Example 8 The surface is uneven 2H 195

[0211] It can be seen from Example 1 and Comparative Example 1 that the addition of the polyurethane dispersion without hydroxyl groups can complement the dispersion containing hydroxyl groups, optimize the leveling and drying speed of the coating, and further reduce the generation of bubbles and pinholes.

[0212] See Figure 1 , Example 1-3, the yield after spraying is extremely high and the surface is very smooth. Figure 2 , Comparative Examples 1 and 2, the presence of a high proportion of pinholes and bubbles, Figure 2 It is a typical form.

[0213] It can be seen from Example 1 and Comparative Example 2 that the present invention selects a polyurethane dispersion with a higher hydroxyl content. After selecting a polyurethane dispersion with a hydroxyl content of 2.1%, the crosslinking density is reduced and the pencil hardness is also reduced. At the same time, due to the reduction in the hydroxyl content, the complementarity between the hydroxyl group and the polyurethane dispersion is affected, resulting in the generation of a small amount of bubbles and pinholes.

[0214] It can be seen from comparative examples 3, 4, and 5 that modified nano-aluminum silicate and blocked polyisocyanate can play a synergistic role, reduce the generation of bubbles and pinholes, and enhance the crosslinking density. The hydroxyl groups or other active groups on the surface of modified nano-aluminum silicate can undergo crosslinking reactions with the released isocyanate groups to form a more compact and stable network structure. The activity of nano-aluminum silicate is further enhanced by surface modification. Figure 3 , Figure 3 This is a common form of defects that occur in Examples 3, 4, and 5.

[0215] It can be seen from comparative examples 6, 7 and 8 that the steps S01: pretreatment of nano-aluminum silicate, S02: thermal reaction treatment, S03: blending modification treatment and S04: high temperature modification treatment can all reduce the generation of bubbles and pinholes and enhance the crosslinking density. The main reason for adopting the above steps is to promote the generation of surface active groups of nanoparticles, thereby promoting crosslinking, optimizing the leveling and drying speed of the coating, and reducing the generation of bubbles and pinholes. Figure 4 , Figure 4 This is a common form of defects that occur in Examples 6, 7, and 8.

[0216] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A water-based two-component electrostatic spray varnish topcoat, characterized in that: It includes component A and component B; 100 parts by weight of hydroxyl-containing aqueous polyurethane dispersion 10-40 parts by weight of hydroxyl-free aqueous polyurethane dispersion 1-3 parts by weight of modified aluminum silicate Conductivity regulator 0.2-2 parts by weight Deionized water 10-30 parts by weight Group B is composed of: Polyisocyanate 20-50 parts by weight Propylene glycol methyl ether acetate 5-20 parts by weight.

2. A water-based two-component electrostatic spray varnish topcoat according to claim 1, characterized in that: The hydroxyl content in the hydroxyl-containing aqueous polyurethane dispersion is 4.5%-6.5%.

3. The water-based two-component electrostatic spray varnish topcoat according to claim 1, characterized in that: The clear varnish topcoat also includes the following components: Thickener 0.1-1 weight part Wetting agent 0.1-1 weight part Leveling agent 0.1-1 parts by weight Defoamer 0.1-1 parts by weight Ultraviolet light absorber 0.1-1 part by weight.

4. The water-based two-component electrostatic spray varnish topcoat according to claim 1, characterized in that: The polyisocyanate consists of 10-30 parts by weight of HDI trimer, 5-10 parts by weight of isophorone diisocyanate, and 5-10 parts by weight of blocked polyisocyanate.

5. The water-based two-component electrostatic spray varnish topcoat according to claim 1, characterized in that: The preparation method of modified nano aluminum silicate is as follows: S01: Pretreatment of Nano-aluminum Silicate The nano aluminum silicate powder is placed in a sufficient amount of sodium hydroxide solution with a mass fraction of 1% to 5% and stirred to mix well for surface activation treatment; This is followed by water washing to remove excess sodium hydroxide; Then, drying treatment is performed to obtain pretreated nano aluminum silicate for standby use; S02: Thermal reaction treatment The nano aluminum silicate powder prepared in S01 is placed in a high temperature environment of 300-350°C for thermal reaction treatment for 20-30 minutes; After the thermal reaction is completed, slowly cool to 200-230°C at a rate of 2-3°C / min and keep at this temperature for 10-30 minutes; Finally, cool to room temperature at a rate of 4-6°C / min and keep warm for later use; S03: Blending and modification Take 5-8 parts of S02 nano aluminum silicate powder, 2-4 parts of silane coupling agent, 0.5-1 parts of nitrate solution and 8-12 parts of surfactant and mix them together; The mixture is subjected to ultrasonic blending to ensure that each component is fully dispersed and uniformly mixed; After the blending ultrasonic treatment is completed, it is set aside; S04: High temperature modification treatment The reserved nano aluminum silicate powder of S03 is heated to 400-500°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min. After cooling to room temperature, it is heated to 500-600°C in an inert atmosphere and reacted for 1-2h at a heating rate of 2-5°C / min. After cooling, the modified nano aluminum silicate is obtained.

6. A water-based two-component electrostatic spray varnish topcoat according to claim 5, characterized in that: After the water washing in S01, the method further comprises the following steps: mixing the pretreated nano-aluminum silicate with a sufficient amount of silicic acid solution with a mass fraction of 2%-5% to perform surface silicification treatment.

7. The water-based two-component electrostatic spray varnish topcoat according to claim 5, characterized in that: The nitrate solution is selected from one or more of a cerium nitrate solution, a zirconium nitrate solution, and a lanthanum nitrate solution.

8. The water-based two-component electrostatic spray varnish topcoat according to claim 5, characterized in that: The silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane.

9. A method for preparing a water-based two-component electrostatic spray varnish topcoat, characterized in that: The electrostatic spray varnish topcoat comprises component A and component B; 100 parts by weight of hydroxyl-containing aqueous polyurethane dispersion 10-40 parts by weight of hydroxyl-free aqueous polyurethane dispersion 1-3 parts by weight of modified aluminum silicate Conductivity regulator 0.2-2 parts by weight Deionized water 10-30 parts by weight Group B is composed of: Polyisocyanate 20-50 parts by weight Propylene glycol methyl ether acetate 5-20 parts by weight; The A and B components are mixed evenly and packaged separately to obtain a water-based two-component electrostatic spray varnish topcoat.